(untitled) - Tatwade, Bandita; Hiwarkar, Monali (Academia Anatomica International, 2019)
Introduction: Cleft hand or Ectrodactyly or Split Hand is a rare form of congenital hand disorder in which there is deficiancy of one or more central rays of the hand. The hand presents with a V-shaped gap situated in the centre of the palm. The condition may occur alone or maybe associated with anomalies of foot, syndactly, polydactyly, triphalangeal thumb, transverse bones in the hand or maybe part of Ectrodactyly Ectodermal dysplasia Cleft (ECC) Syndrome. Aims and Objectives: To find out the sex ratio and incidence of laterality (unilateral or bilateral) of cleft hand in North East population of Assam. Subjects and Methods: This study included 31 children between age group of 3 years to 8 years with hand deformities who were brought to the Plastic Surgery Department, Gauhati Medical College, Guwahati for aesthetic correction within a time span of 2 years. Only those cases who had central defects of hand were included & those with other syndromic anomalies were excluded. For this detailed clinical and radiological examination was done to evaluate the extent of bone or tissue involvement and to find out any syndromic association of the condition. Results: Out of 31 cases, 10 cases were had Unilateral and 21 cases had Bilateral Cleft Hands. It was seen that out of 31 cases, 22 were males and only 09 were females indicating that male to female ratio of the deformity is 2.44 .Thus, males were more affected than females. Conclusion: Most of the cases presented with absence of the middle finger and central tissue of the affected hand since birth. The embryological basis has been highlighted to throw light into such a catastrophe where both males and females were affected and showed unilateral or bilateral involvement of the hand leading to cosmetic and functional debility. Therefore, the study revealed that males were more affected than females and bilateral involvement of the hands were common than unilateral involvement.